Comparison on Efficiency and Speed of 2-Tier And 3-Tier OLTP Systems - Teduh Dirgahayu; Muhammad Indra Utama (Department of Informatics,Faculty of Industrial Technology,Islamic University of Indonesia, 2004)
Online Transaction Processing (OLTP) systems are characterized by a large number of users accessing online data simultaneously. Available architectures for distributed OLTP systems are 2-tier and 3-tier client/server architecture. Two major factors that have to be considered in deciding architecture of an OLTP system are resource efficiency and speed. This research aimed to compare those two different architectures on efficiency and speed. As a test bed, we developed 2-tier and 3-tier web-based application for online banking using Microsoft COM+ and ASP. We then tested them using Microsoft Web Application Stress Tool. Our components were designed into two layers: Business Access Layer (BAL) and Data Access Layer (DAL). The results show us that there was a trade-off on resource efficiency and system’s speed. The 2-tier OLTP system gave us better speed performance but lower resource efficiency. On the other hand, the 3-tier system offered more efficient resource utilization i.e. it saved 62% - 64% of the connection needed for 2-tier system, but its speed reduced at about 24% than the speed of 2-tier system. Further research is needed to examine more number of concurrent users in longer test duration so as to get realistic behaviors of large OLTP systems.